MR Imaging of the Acoustic Nerves and Small Acoustic Neuromas at 0.6 T: Prospective Study - New, Paul F. J.; Bachow, Terry B.; Wismer, Gary L.; Rosen, Bruce R.; Brady, Thomas J. (American Journal of Neuroradiology, 1985)
To evaluate the capability of magnetic resonance (MR) in imaging normal acoustic nerves, 12 volunteers without signs or symptoms of intracranial disease were examined using a 0.6 T superconductive system. Several spin-echo (SE) pulse sequences were tested to identify the optimal sequence for demonstration of the acoustic nerve bundle. Repetition times (TRs) varied from 300 to 2000 msec and echo times (TEs) from 30 to 120 msec. A single-slice technique was used with 5 and 8 mm sections, one or two data acquisitions per projection, and axial and coronal imaging. The normal acoustic nerves were demonstrated readily by MR in axial and/or coronal sections. The distal parts of the nerves and tumors were imaged best with SE 1500/60. The medial extremities of the seventh and eighth nerves tended to be obscured in this sequence by brightening the cerebrospinal fluid signal adjacent to the brainstem, but they were demonstrated clearly with 500 or 800 msec TR and 30 msec TE. Five patients were studied who had hearing loss and evidence of retrocochlear disease. In four patients, MR imaging demonstrated five acoustic nerve tumors ranging in size from purely intracanalicular to a 12 mm cisternal component. In the fifth case, no tumor was identified by MR imaging or gas computed tomographic (CT) cisternography. Contrast-enhanced CT using a Siemens Somatom DR 3 or GE CT/T 8800 scanner failed to provide convincing evidence of tumor in any case, while gas CT cisternography was positive in all five tumors. All five acoustic neuromas were identified readily using the SE sequences that proved optimal for demonstration of normal nerves. This experience revealed that MR imaging can demonstrate the eighth nerve complex well and reliably. Single-slice (5 or 8 mm) technique is adequate, but multislice without tissue gaps (used recently) is more efficient. Small, even intracanalicular, acoustic neuromas are imaged effectively, indicating that the method is capable of superseding contrast CT cisternography, particularly with improving technology.